2006
DOI: 10.1002/app.24389
|View full text |Cite
|
Sign up to set email alerts
|

Rheological properties of ethylcellulose latex

Abstract: Because of their large specific surface area, aqueous-based pseudolatex systems of ethylcellulose can absorb large amounts of drugs. In addition, the stability of polymeric particles in biological fluids delays the release of the drug as in controlled drug delivery systems. The aim of the present study was to characterize the rheological properties of latex particles as a measure of their colloidal stability. Here, we report the effect of three variables: pH, electrolyte concentration, and temperature. The rhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In the field of emulsions, ethyl cellulose can be used as an emulsifier, 9 incorporated into coatings [10][11] or used to elaborate microspheres notably for drug delivery applications. [12][13][14] The most developed procedure for the preparation of EC pseudo-latexes relies on either the emulsification/solvent evaporation (ESE) process [15][16] (which consists in the dissolution of EC in a suitable solvent, its subsequent emulsification into water phase containing suitable emulsifying agent, and finally the solvent evaporation) or miniemulsification. 17 A process based on nanoprecipitation has also been reported.…”
mentioning
confidence: 99%
“…In the field of emulsions, ethyl cellulose can be used as an emulsifier, 9 incorporated into coatings [10][11] or used to elaborate microspheres notably for drug delivery applications. [12][13][14] The most developed procedure for the preparation of EC pseudo-latexes relies on either the emulsification/solvent evaporation (ESE) process [15][16] (which consists in the dissolution of EC in a suitable solvent, its subsequent emulsification into water phase containing suitable emulsifying agent, and finally the solvent evaporation) or miniemulsification. 17 A process based on nanoprecipitation has also been reported.…”
mentioning
confidence: 99%
“…High temperature also caused a change in particle shape. [11] Viriyaroj et al . in 2009 reported that carboxymethyl cellulose, methylcellulose and xanthan gum used as a suspending agent caused desirable rheological behavior Xanthan gum exhibits plastic or pseudoplastic flow and this behavior was possibly a result of shearing action on the long chain molecule of xanthan gum.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that viscoelastic behavior was affected by temperature. High temperature also caused a change in particle shape (14). Moreria et al in 2010 investigated influence of oleic acid on the rheology and in vitro release of lumiracoxib from poloxamer gels.…”
Section: Discussionmentioning
confidence: 99%